O Mestre e o Psicanalista: tecendo laços nas políticas públicas - NICOLAU, Roseane Freitas (Universidade do Estado do Rio de Janeiro, 2023)
The psychoanalytic discourse insertion into public health institutions causes some technical and ethical deadlocks for confronting the singularity of “an individual”, that is an aim of psychoanalysis, to the kind of healthcare employed by public policies of attention and care “for all” users of certain categories. This fact has made many psychoanalysts to wonder about important points of this experience, for example the role of subject in healthcare services, whose emergency gets subservient to the master’s discourse, which structures the institutional relations. How to keep the specificity of the psychoanalytical praxis in the institutional context, in which bonds are structured by the master’s discourse? How do agreements and disagreements between discourses of master and psychoanalyst happen? The Psychoanalysis, according to the Freudian-Lacanian orientation, responds to these issues taking into account the analyst's discourse peculiarity and treatment of the subject of the unconscious from what Lacan called psychoanalysis applied to therapy, which makes possible the inclusion of psychoanalysis the institution.